2018
DOI: 10.4314/agrosh.v18i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Economics of small-scale maize production in Toto local government area, Nasarawa state, Nigeria

Abstract: The study examined the economics of small-scale maize production in Toto Local Government Area of Nasarawa State, Nigeria. A two-stage sampling technique was adopted for the data collection. Descriptive statistics, regression and gross margin analyses were used to analyse the data collected. The study revealed that majority of the respondents were within the active working age and most of them (83%) were male. The majority of the respondents were married and had a household size of five persons and farm size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
3
11
1
Order By: Relevance
“…On the aggregate, the majority (86.17%) of the farmers were married and 5.79, 5.47 and 5.67% were widowed, single and divorced, respectively. This finding is in line with the report of Girei et al. (2018) who opined that married farmers are likely to be committed to increasing the yield on their farms as it is critical to the sustenance of their family.…”
Section: Resultssupporting
confidence: 90%
“…On the aggregate, the majority (86.17%) of the farmers were married and 5.79, 5.47 and 5.67% were widowed, single and divorced, respectively. This finding is in line with the report of Girei et al. (2018) who opined that married farmers are likely to be committed to increasing the yield on their farms as it is critical to the sustenance of their family.…”
Section: Resultssupporting
confidence: 90%
“…Return per naira shows that 87 kobo was earned for each additional investment made; showing that smallscale maize production in the study area was profitable. This is consistent with the finding of [12] and [11] where the gross margin was estimated at 132 751.23 and the return per naira invested was estimated at 1.99. This meant that a return of PAR2 was obtained for each PAR1 invested.…”
Section: B Gross Margin Analysis For Maize Profitability In the Study Areasupporting
confidence: 93%
“…The increase in farm size and labor will lead to an increase in output. The result of this double log function is in contrast to the double log result of [11] where the calculated R 2 was 0.76, indicating that the variation in the output level was accounted for by the explanatory variables in the model. The double log result also showed that only the labor force had a positive coefficient, which was significant at 1%.…”
Section: Relationship Between the Maize Production Output And The Socio-economic Characteristics Of The Maize Small-scale Farmerscontrasting
confidence: 70%
See 1 more Smart Citation
“…Hence, millions of tons of corn cob are dumped as waste annually, constituting environmental pollution. It was reported by Gireiet al [40] that Nigeria produced about 10.5 million metric tons of maize in 2016/2017. Finding an economic utilization of this agro-waste is a valuable research exercise.…”
Section: Introductionmentioning
confidence: 99%